Clinical and Microbiological Characteristics of a Community-Acquired Carbapenem-Resistant Escherichia coli ST410 Isolate Harbouring blaNDM-5-Encoding IncX3-Type Plasmid From Blood - Gu, Ji-Na; Chen, Lin; Weng, Xing-Bei; Yang, Xiao-Yan; Pan, Dan-Mei (Frontiers in Medicine, 2021)
Objectives: The aim of this research was to investigate the clinical and microbiological characteristics of a case of community-acquired carbapenem-resistant Escherichia coli isolated from a patient with a bloodstream infection in China. Methods: E. coli Huamei202001 was recovered from the first blood culture from a patient hospitalized in China. A antimicrobial susceptibility test was performed, and the genome was sequenced on an Illumina HiSeq Xten platform with a 150-bp paired-end approach. The generated sequence reads were assembled using Unicycler, and the whole-genome sequence data were analysed using bioinformatics tools. Moreover, the patient and her main family members obtained a faecal sample screening test for CRE, the positive strain was further isolated, and the identification and antimicrobial susceptibility testing was performed. Results: E. coli Huamei202001 belonged to sequence type 410. In addition, a blaNDM-5-encoding IncX3-type plasmid was responsible for the spreading of carbapenem resistance. Only the patient was detected as having a positive faecal sample screening test for CRE. Strain Fec01 was identified as E. coli, and the antibiotic susceptibility profile was the same as that of E. coli Huamei202001. Conclusions: E. coli Huamei202001 is defined as community-acquired carbapenem-resistant Enterobacteriaceae. The clone ST410 that harbours the blaNDM-5-encoding IncX3-type plasmid is causing new high-risk clones globally. Thus, infection control measures should be strengthened to curb the dissemination of IncX3.